Functional and Morphological Findings in Early and Advanced Stages of HIV Infection: a Comparison of 99mTc-HMPAO SPECT with CT and MRI Studies - Tatsch, K.; Schielke, Eva; Bauer, W. M.; Markl, A.; Einhäupl, K. M.; Kirsch, C.-M. (Nuklearmedizin - NuclearMedicine, 1990)
In fourty patients at early and advanced stages of HIV infection (Walter Reed stages I—VI) regional cerebral blood flow was determined by 99mTc-HMPAO SPECT, comparing the results with CT and MRI findings. All patients with HIV encephalopathy (AIDS dementia complex) had pathologic SPECT results (multilocular, patchy uptake defects), but also in earlier and even earliest stages of HIV infection positive SPECT findings were observed. Compared to functional SPECT imaging, morphologically orientated methods (CT, MRI) were insensitive in detecting HIV-induced foci: more than 50% of the patients with pathologic SPECT findings had negative CT or MRI scans. Most patients in advanced Walter Reed stages had neurological abnormalities accompanied by positive SPECT. Subtle alterations of HMPAO uptake were observed even in a few cases of early HIV infection without neurological CNS symptoms. The data presented suggest that HMPAO SPECT is highly sensitive in the detection of altered brain perfusion not only in advanced but also early stages of HIV infection. Changes in regional cerebral blood flow are present before noticeable structural defects may be observed. Thus, it is suggested to use HMPAO SPECT in the evaluation and monitoring of patients with, and particularly at risk for, HIV encephalopathy.Bei 40 Patienten in frühen und fortgeschrittenen Stadien der HIV-Infektion (Walter-Reed-Stadien I-VI) wurde mit 99mTc-HMPAO-SPECT der regionale zerebrale Blutfluß untersucht und die Ergebnisse dem jeweiligen CT- und MR-Befund gegenübergestellt. Alle Patienten mit manifester HIV-Enzephalopathie (AIDS-De- menz-Komplex) hatten pathologische SPECT-Befunde (multilokulare Speicherdefekte), aber auch in frühen und sehr frühen Stadien der HIV-Infektion wurden bereits positive SPECT-Befunde erhalten. Im Gegensatz zu der funktionsorientierten SPECT-Un- tersuchung erwiesen sich die morphologisch ausgerichteten Diagnoseverfahren (CT, MR) als wenig sensitiv beim Nachweis HIV-induzierter Foci: Mehr als 50% der Patienten mit pathologischen SPECT-Ergebnissen zeigten unauffällige CT- bzw. MR-Befunde. Die Mehrzahl der Patienten im fortgeschrittenen Walter-Reed- Stadium war bei pathologischem SPECT-Befund auch neurologisch auffällig. Speicherdefekte von geringerem Ausmaß traten bereits bei einigen Patienten im Frühstadium und ohne ZNS-Symptomatik auf. Nach den vorliegenden Daten stellt HMPAO-SPECT ein hochsensitives Nachweisverfahren für zerebrale Perfusionsstörungen nicht nur in fortgeschrittenen, sondern auch frühen Stadien der HIV-Infektion dar. Änderungen des regionalen zerebralen Blutflusses sind nachweisbar, bevor morphologische Defekte faßbar werden. Untersuchungen mit HMPAO-SPECT bieten sich daher zur Abklärung und Verlaufsbeobachtung von Patienten mit und insbesondere bereits bei Verdacht auf HIV-Enzephalopathie an.